DAMPAK KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN SWASTA DI PEKANBARU - Warman, Defi; Iskandar, Iskandar (Jurnal Daya Saing, 2025)
Human resources in an organization are a very important determinant of the effectiveness of activities within the organization. Human resources in an organization are people who provide their energy, talent and creativity to the organization. Every organization always tries to improve employee performance, with the hope that the goals of the organization will be achieved. This study aims to determine whether compensation and career development have a significant effect on the performance of private employees in Pekanbaru. The research method uses multiple linear regression analysis. The population is 32 employees and all of them are used as samples. The results of the study show that compensation and career development simultaneously have a significant effect on employee performance. Compensation and career ladder partially have a significant effect on employee performance. For leaders, further improve the provision of compensation in the organization so that employee performance becomes better. Keywords: Compensation, Career Ladder, Performance